2020
DOI: 10.3389/fpsyg.2020.00765
|View full text |Cite
|
Sign up to set email alerts
|

Current Research on the Impact of Foreign Language Learning Among Healthy Seniors on Their Cognitive Functions From a Positive Psychology Perspective—A Systematic Review

Abstract: The purpose of this review study is to explore the existing research focusing on the impact of foreign language learning among healthy seniors on their cognitive functions from the positive psychology perspective. The methods are based on a literature review of available sources found on the research topic in two acknowledged databases: Web of Science and Scopus. The search period was not limited by any time period since there are not many studies on this topic. Altogether seven original studies were detected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…Furthermore, the participants in the experimental group benefited from the very positive social ties within their group [ 34 , 35 ], gaining self-confidence and motivation to continue studying English at the University of the Third Age. As Klimova and Pikhart [ 10 ] believe, it is especially social and psychological well-being through which the cognitive benefits of foreign language learning might be observed as foreign language learning represents for seniors a new purpose of their life. This has also been evidenced by recent findings on the theory of positive psychology and foreign language learning by older adults [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the participants in the experimental group benefited from the very positive social ties within their group [ 34 , 35 ], gaining self-confidence and motivation to continue studying English at the University of the Third Age. As Klimova and Pikhart [ 10 ] believe, it is especially social and psychological well-being through which the cognitive benefits of foreign language learning might be observed as foreign language learning represents for seniors a new purpose of their life. This has also been evidenced by recent findings on the theory of positive psychology and foreign language learning by older adults [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies on the effects of foreign language learning on improving cognitive reserve and health in old age have been few and far apart [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Overall, the findings of these studies indicate that foreign language learning may enhance cognitive performance among healthy older individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, as Formosa (2019) states, maintaining cognitive skills and expanding social contacts are the most common reasons for attending such a course. Klimova and Pikhart (2020) report that it is especially through social and psychological wellbeing that the cognitive benefits of FLL might be observed, since FLL can be for seniors another new purpose of their life. Nevertheless, research also shows that although older adults seem to be highly motivated in conducting meaningful tasks, high motivation is not sufficient for their better performance ( Ceccato et al, 2019 ).…”
Section: Computer-based Foreign Language Training For Healthy Individmentioning
confidence: 99%
“…Furthermore, it has been evidenced that their cognition and emotions are inseparable phenomena (Swain, 2013 ). Research (Klímová and Pikhart, 2020 ) also shows that both cognitive and non-cognitive functions in FLL significantly differ across generations. Although it is known that adults can master a foreign language even in later age, it was proved that cognitive functions decline with an advancing age (Murman, 2015 ).…”
Section: Introductionmentioning
confidence: 95%
“…At present, there is not much research comparing foreign results in well-being outcomes of foreign language learning (FLL) among healthy older adults. The recent review paper of Klímová and Pikhart ( 2020 ), however, revealed that FLL might have a positive impact on the maintenance and/or enhancement of cognitive abilities irrespective of age. In particular, FLL courses seem to offer new opportunities to healthy seniors for socialization and integration into society, which may positively affect their overall well-being.…”
Section: Introductionmentioning
confidence: 99%